Cobalt–borate nanowire array as a high-performance catalyst for oxygen evolution reaction in near-neutral media. Issue 16 (4th April 2017) - Ren, Xiang; Ge, Ruixiang; Zhang, Yong; Liu, Danni; Wu, Dan; Sun, Xu; Du, Bin; Wei, Qin
Abstract : As a durable catalyst, cobalt–borate nanowire array on Ti mesh exhibits high activity for water oxidation in near-neutral media, thereby achieving a geometrical catalytic current density of 10 mA cm −2 at an overpotential of 420 mV. Abstract : The development of an efficient catalyst for electrolytic water oxidation under neutral or near-neutral environment remains a great challenge. In this communication, we developed a high-performance cobalt–borate nanowire array on a Ti mesh (Co–Bi NA/Ti) from a CoSe2 nanowire array via rapid topotactic conversion. As a three-dimensional water oxidation electrode, such Co–Bi NA/Ti, demands only 420 mV to drive a geometrical catalytic current density of 10 mA cm −2 . It exhibits superior activity when compared to most of the reported non-precious metal catalysts working under benign conditions. In addition, Co–Bi NA/Ti also displays good stability and high turnover frequency (0.59 s −1 at an overpotential of 600 mV) in 0.1 M potassium borate (pH: 9.2). This novel research finding has paved a new path for developing highly active oxygen evolution reaction electrocatalysts in near-neutral media.